Analysis of Marketing Mix Element Affecting Medical Tourism - Natalia, Tiara Edithia; Sulistiadi, Wahyu (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2019)
Medical tourism sector, for third world nowadays, is a multifactorial sector that has slowly risen to the point of becoming one of the industries that produces income and pretty competitive in the world, and also has been considered as sophisticated tourism in modern field. This study aims to investigate the elements of the marketing mix and other factors that influence medical tourism. Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA) was used in this study From 11 articles reviewed, it’s found that almost all of the marketing mix element were related to medical tourism in a country. Some of the articles stated that factors like product offered, price, place, and promotion were related to medical tourism in a country. The conclusion from this study is that marketing mix element in general and other factors like regulations, number and skills of medical staffs and health services affected medical tourism significantly.